Study ff Interaction Between ADT-C2 Cyclic Peptide (Ac-CADTPPC-NH2) and E-Kadherin Protein Using Docking Molecular Method - Panduwati, Digna Renny (ALKIMIA, 2021)
Research has been conducted on the study of the interaction between cyclic peptide ADTC2(Ac-CADTPPC-NH2) and E-cadherin protein using the molecular docking method. The aim of this study is to determine the position of the binding site and the energy of interaction between the ADTC2 peptide and the EC1-EC2 domain of E-kadherin. This research was divided into two parts, (1) Preliminary test using molecular dynamics (DM) method with Gromacs v4.5.4 software, (2) interaction of the peptide ADTC2 with EC1-EC2 using the molecular docking method (MD) with Autodock 4.2 software. Docking was performed with the blind dock method on EC1 and EC2 position. In the second step, the gridbox position was reduced based on the binding activity between E-cadherin and peptides. The strongest interaction and Van der Walls bonds were obtained in boxes B, C and D. The results showed that the ADTC2 peptide had a biological activity to inhibit the interaction of E-cadherin...E-cadherin by forming a complex with the EC1-EC2 domain. This inhibition occured by forming two binding sites in the EC1 domain (interaction energies are -23.309 kJ / mol and -26.234 kJ / mol, respectively) and one binding site in the EC2 domain (interaction energies are -22.677 kJ / mol). Based on preliminary tests, it can be proven that the native structure of ADTC2 is cyclic with optimization energy of -52504.78 kJ/mol and very stable from the beginning to the end of DM with an RMSD was <2 Å.